MANFAAT PERNIKAHAN POLIGINI BAGI KAUM PEREMPUAN - Pawitasari, Erma (IAIN Ponorogo, 2015)
Abstract: Marriage, as one of the subject domains of Islamic studies, often led to problems in a number of cases if it is related to polygamy. Polygamy was often only seen from the perspective of the needs and the existence of man. Wives who accepted polygamy were synonymous with stigma called